Is "Seven Sisters" Mistranslation of "六个姐姐 "?—A Second Defense of Howard Goldblatt's "Seven Sisters" - Deng, Wensheng (Forum for Linguistic Studies, 2025)
In the context of "Chinese-Cultures-Go-Global," effectively communicating Chinese culture to the world has become a significant challenge. Numbers in literary and cultural texts are not merely quantitative markers but carriers of emotions, thoughts, and cognitive connotations, making the translation of numbers an increasingly important area of focus. Drawing on the prototype theory in cognitive linguistics, with an empirical survey, this paper offers an additional defense of Howard Goldblatt's translation of "六个姐姐 (liù gè jiě jie)" as "seven sisters". First, the paper explores and explains the rationale behind Goldblatt's choice of "seven sisters," arguing that "seven sisters" is more typical than "six sisters" because it embodies more core features of the source text, while the latter exhibits more peripheral ones of the source text. Second, the paper proposes a new standard for evaluating a literary translation: The core feature—fidelity to the source text—takes precedence over other factors; diversified versions of translations (i.e., "seven sisters" and "six sisters") belong to a family category of varied versions of the original. Evaluating the versions requires balancing core and peripheral features rather than solely emphasizing fuzzy fidelity to the original, which is adhered to by traditional translation studies, and the assessment of literary translation becomes more objective than before. By conducting a comparative analysis of the cultural connotations and cognitive characteristics of the source and target texts, this paper not only defends Goldblatt's translation choice but also provides new theoretical supports for translating numbers in literary texts and a new literary translation standard. It is both realistic and valuable for literary translation studies as well as constructive to cross-cultural communication.